2003
DOI: 10.1007/s00105-002-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

Benignes zellreiches fibröses Histiozytom der Großzehe mit knöchernen Defekten des Nagelkranzfortsatzes

Abstract: Fibrohistiocytic tumors are characterized by the presence of fibroblast like spindle cells and histiocytes. The benign fibrous histiocytoma (dermatofibroma, BFH) as well as the malignant dermatofibrosarcoma protuberans (DFSP) and the malignant fibrous histiocytoma (MFH) belong to this group. A recurrent painful, hard 2 cm tumor on the left hallux of a 54-year-old woman led to an erosion of the underlying phalanx. The patient had suffered from ingrown toenails for more than 10 years. Histologically there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[ 15 ] It shows diffuse positivity for CD34 rather than factor XIIIa. [ 16 ] In this study, results of immunohistochemistry showed the expression of factor XIIIa and α-smooth muscle actin in the CFH lesion. Factor XIIIa has been proposed to react with dendritic cells and is intensely expressed in cutaneous histiocytomas.…”
Section: Discussionmentioning
confidence: 57%
“…[ 15 ] It shows diffuse positivity for CD34 rather than factor XIIIa. [ 16 ] In this study, results of immunohistochemistry showed the expression of factor XIIIa and α-smooth muscle actin in the CFH lesion. Factor XIIIa has been proposed to react with dendritic cells and is intensely expressed in cutaneous histiocytomas.…”
Section: Discussionmentioning
confidence: 57%